Shaping resilience: Gender insights on weather and climate information services in East Africa - Ouya, Fredrick; Lutomia, Cosmas; Mvuyibwami, Patrick; Byandaga, Livingstone; Kagabo, Desire; Nchanji, Eileen (2024)
Climate shock and stressors like floods and droughts affect agriculture in East Africa, where erratic weather patterns threaten agricultural productivity and rural livelihoods. These impacts are disproportionately felt by women, youths, and other vulnerable groups like refugees, internally displaced persons (IDPs), and persons living with disabilities (PLWDs). The above-mentioned group of persons often have a low resilience to climate change hazards. Limited resource access, restrictive cultural norms and socioeconomic barriers often constrain their adaptive capacity. This study assesses communities' access to, use and impact of Weather and Climate Information Services (WCIS) in four East African countries - Kenya, Rwanda, Uganda, and Tanzania. The study used a qualitative research design, employing Focus Group Discussions (FGDs) and Key Informant Interviews (KIIs) to capture diverse respondents’ perspectives. A total of 34 FGDs (17 men, 16 women, and 1 mixed FGD) were conducted with farmers. Additionally, 98 KIIs (69 men and 29 women) were conducted with representatives of farmer cooperatives, NGOs, media, government officials (national metrological and hydrological services), scientists from the ministry, etc. This study revealed significant gendered disparities in accessing and utilising Weather and Climate Information Services (WCIS) across Kenya, Tanzania, Rwanda and Uganda. Men, women, and youths mainly accessed WCIS through television, radio, extension officers, and social media platforms like YouTube. Due to gender norms, additional information was obtained by men from the public meetings and community leaders; women, constrained by domestic responsibilities, got information from community meetings like savings groups and community networks. They also get information from informal discussions with family and friends. On the other hand, youth predominantly prefer social media but exhibit mixed trust toward agriculture-related information. Persons with disability or internally displaced persons have limited or often no access to assets – mobile phones, television and radios - that can be used to access climate and weather information. Youths also have resource limitations, like persons living with disabilities (PLWDs). WCIS provided farmers with information that resulted in timely planting, selecting the most suitable variety and the type of seeds to grow depending on the climate. It also influenced farmers to adopt sustainable practices like water conservation, crop rotation, and soil conservation, resulting in improved yields, reduced post-harvest losses, and enhanced food and nutrition security. Men dominate household decision-making, limiting women’s ability to act on climate information effectively. Limited access to technology and scepticism about forecast accuracy persist among farming communities. In Tanzania, accurate and localized forecasts in most regions have improved agricultural productivity and income compared to other countries. However, most rural areas are characterised by limited infrastructure and inequitable gender roles that restrict efficient access to WCIS. Participants across FGD and KII called for strengthening partnerships and collaborations between the Meteorology Agency, NGOs, and local leaders and a need to integrate indigenous knowledge with modern scientific data, delivered in a way that farmers can use it for their different crops and livestock. This study underscores the critical role of WCIS in building the resilience of farmers, prioritizing inclusive governance, community-driven approaches, and targeted investments; stakeholders can ensure that WCIS is delivered in an inclusive manner, particularly targeting those from marginalized and vulnerable groups, in adapting to the challenges of climate change. While WCIS has the potential to transform livelihoods and enhance climate resilience, systemic barriers that are often gendered must be addressed to achieve equitable outcomes. By prioritising inclusivity, fostering partnerships, and leveraging community knowledge, WCIS can empower vulnerable populations, drive sustainable development, and transform agricultural resilience across East Africa. This study also recommends developing synergies and partnerships to institutionalise WCIS in all country programs/projects and working with women and youth to drive climate resilience in rural areas. Initiatives supporting joint household decision-making and community-based climate-smart practices have improved productivity and reduced intra-household and family disputes.